Discovery of New Polymorphs of Gallium Oxides with Particle Swarm Optimization‐Based Structure Searches. (10th May 2020) - Wang, Xue; Faizan, Muhammad; Na, Guangren; He, Xin; Fu, YuHao; Zhang, Lijun
Abstract: Gallium oxide (Ga2 O3 ) has attracted significant research interest for next‐generation high‐efficiency power devices because of its unique electronic properties such as ultra‐wide band gap, high breakdown electric field, and large Baliga's figure of merit. Ga2 O3 crystallizes in a series of reported polymorphs including β‐, α‐, ε‐, κ‐, γ‐, and δ‐Ga2 O3, the structures of some of which are still in serious controversy. A polymorph structure search study of Ga2 O3 is herein performed by combining particle swarm optimization with first‐principles energetic calculations. In addition to producing the predominant experimental known phases of β‐, α‐, and κ‐Ga2 O3, two new polymorphs are found with space group P 1 ¯ and Pmc 21 consisting of four‐ and five‐fold coordinated Ga. They show comparable energy with β‐ and α‐Ga2 O3 with the energy difference of several meV per atom, and exhibit robust phonon stability. Similarly, the new phases show quite wide band gaps and small electron effective masses by comparing it with other known phases. The Pmc 21 phase shows a calculated spontaneous polarization of 0.277 C m −2, close to that of ε/κ‐Ga2 O3 . The systemic structure searches also establish a structural relationship between ε‐Ga2 O3 and κ‐Ga2 O3 and how the electronic properties vary with polymorphic phase change. Abstract : New polymorph structures of Ga2 O3 are searched by combining particle swarm optimization algorithm with first‐principles energetic calculations. In addition to the known phases, two new energetically favored phases are predicted, exhibiting reasonably wide band gap, small electron effective mass, and unexpected spontaneous electronic polarization.